2019
DOI: 10.1515/hf-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic vapour sorption protocols for the quantification of accessible hydroxyl groups in wood

Abstract: This study investigated several key parameters of deuterium exchange measurements in a dynamic vapour sorption apparatus to optimise the measurement protocol for hydroxyl (OH) group accessibility determination. The impact of changing the sample mass, the deuterium oxide (D2O) vapour exposure time and the rate of change in moisture content (dm dt−1) during the drying steps on the measured OH group accessibility were analysed. A sample mass of more than 10 mg, an exposure to D2O vapour of at least 10 h and a dm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…One may assume that the intermediate drying step between deuteration and re-protonation resulted in the entrapment of some D 2 O or OD groups within the cell wall. Drying has been shown to trap solvents within the wood structure (Uimonen et al 2020). However, an additional measurement sequence during which the intermediate drying step was omitted, so that the reprotonation in H 2 O vapor for 24 h at 95% RH directly followed after the deuteration in D 2 O vapor, resulted in nearly the same number of remaining OD groups (see Supplementary Fig.…”
Section: Re-protonation After Deuteration In D 2 O Vapormentioning
confidence: 99%
See 3 more Smart Citations
“…One may assume that the intermediate drying step between deuteration and re-protonation resulted in the entrapment of some D 2 O or OD groups within the cell wall. Drying has been shown to trap solvents within the wood structure (Uimonen et al 2020). However, an additional measurement sequence during which the intermediate drying step was omitted, so that the reprotonation in H 2 O vapor for 24 h at 95% RH directly followed after the deuteration in D 2 O vapor, resulted in nearly the same number of remaining OD groups (see Supplementary Fig.…”
Section: Re-protonation After Deuteration In D 2 O Vapormentioning
confidence: 99%
“…The closed the cell wall pores in the dried wood may have not fully re-opened during re-soaking, particularly after the first drying of neverdried wood. This could have resulted in the inaccessibility of some OD groups (Suchy et al 2010) or an entrapment of D 2 O within the cell wall structure (Uimonen et al 2020). However, when the deuterated sections were not dried, but immediately washed in liquid H 2 O for ca.…”
Section: Re-protonation After Deuteration In Liquid D 2 Omentioning
confidence: 99%
See 2 more Smart Citations
“…By determining the difference in dry mass of the sample before and after conditioning, one can calculate the moles of accessible hydroxyl groups in the sample from the difference in the molar mass of hydrogen and deuterium. For untreated, acetylated and furfurylated wood, a 10-hour D 2 O conditioning period is sufficient for the samples to reach equilibrium [32,35,36,38,62]. However, preliminary trials with SCA-modified wood showed sample mass had not stabilised after 10 h of D 2 O conditioning.…”
Section: Preliminary Sorption Experimentsmentioning
confidence: 99%